If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3q + 52q + -5 = 65 Reorder the terms: -5 + 3q + 52q = 65 Combine like terms: 3q + 52q = 55q -5 + 55q = 65 Solving -5 + 55q = 65 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 55q = 65 + 5 Combine like terms: -5 + 5 = 0 0 + 55q = 65 + 5 55q = 65 + 5 Combine like terms: 65 + 5 = 70 55q = 70 Divide each side by '55'. q = 1.272727273 Simplifying q = 1.272727273
| 11-5x=4x-20 | | 25x^2-294x+945=0 | | x-8=10.2 | | x-8=10.2 | | 4x*7x^2*(5x^3)= | | x-1-2-3=1+3-5 | | 4+10=-26 | | x^3+2x^2+2x+4=0 | | 3(-6)+x-5=-8(-4) | | (2x-3)(2x-3)-(4x-1)(4x-1)= | | x^25+2=0 | | d+6-3= -3 | | x-3(-6)=-6(-2) | | 50+12x=30+15x | | -1*3+1=-7 | | 8x-12x=4x-4 | | (4w+2)(6+w)=0 | | x+25=15-28 | | 3*5+22=28 | | (x)+4=12 | | (p)-5=10 | | 20-x=50 | | x/61068,40=183 | | 8-(r)=-2 | | 11=-5+8 | | -16=-2(q) | | 2-7=9 | | 3x+52=5x+6 | | (14-22)=4y | | 7-3=34 | | c^2+c=0 | | (6+v)(4v-5)=0 |